Factors affecting the regulation of pacing: current perspectives - Mauger AR (Dove Medical Press, 2014)
Alexis R Mauger Endurance Research Group, School of Sport and Exercise Sciences, Faculty of Science, University of Kent, Chatham, UK Abstract: During prolonged dynamic and rhythmic exercise, muscular pain and discomfort arises as a result of an increased concentration of deleterious metabolites. Sensed by peripheral nociceptors and transmitted via afferent feedback to the brain, this provides important information regarding the physiological state of the muscle. These sensations ultimately contribute to what is termed "exercise-induced pain". Despite being well recognized by athletes and coaches, and suggested to be integral to exercise performance, this construct has largely escaped attention in experimental work. This perspective article highlights the current understanding of pacing in endurance performance, and the causes of exercise-induced pain. A new perspective is described, which proposes how exercise-induced pain may be a contributing factor in helping individuals to regulate their work rate during exercise and thus provides an important construct in pacing. Keywords: pain, exercise-induced pain, discomfort, exercise performance, self-paced